The occurrence of postpartum depression in women at puerperium and the sociodemographic situation and family relationships - Lewicka, Magdalena; Sulima, Magdalena; Iracka, Emilia; Makara-Studzińska, Marta (Current Problems of Psychiatry, 2012)
Introduction. Pregnancy and childbirth are the periods where there are mood swings and hormonal changes in the female body. The development of depression during the postpartum period is about ten times higher than in other times. Aim. The aim of this study was to analyze the occurrence of postpartum depression in women in the postpartum period, depending on sociodemographic situation and family relationships. Materials and methods. The study was conducted among 130 women in childbirth, between the fourth and twelfth week of childbirth. Research tool used was the author questionnaire and The Edinburgh Postnatal Depression Scale (ESDP, called Edinburgh postnatal Depression Scale). Results. Based on studies of postpartum, depression was found in 40.00% of respondents, while 60.00% of the women h ad no symptoms of postpartum depression. In addition, a significant association was found between the occurrence of postpartum depression and age (p=0.03) and marital status (p=0.0006). A significant correlation was also shown between the presence of depressive symptoms and the assessment of the relationship with a partner (p=0.00001), with their parents (p=0.0006) and in-laws (p= 0.008). Conclusions. Age, marital status and family relations have a significant impact on the prevalence of depressive symptoms in the postpartum period. Particular attention should be drawn to mothers under 25 years of age, unmarried, and those that have a bad relationship with their husbands/partners, their parents and in-laws. Women diagnosed with depression levels ≥ 12 points, should be taken into the care of a psychologist or psychiatrist to confirm or exclude postpartum depression. Family midwives and nurses should use screening tool in professional practice to identify patients with depressive disorders at puerperium.